Critical appraisal of the piRNA-PIWI axis in cancer and cancer stem cells - Elena Garcia-Borja; Frantisek Siegl; Rosana Mateu; Ondrej Slaby; Aleksi Sedo; Petr Busek; Jiri Sana (BMC, 2024)
Abstract Small noncoding RNAs play an important role in various disease states, including cancer. PIWI proteins, a subfamily of Argonaute proteins, and PIWI-interacting RNAs (piRNAs) were originally described as germline-specific molecules that inhibit the deleterious activity of transposable elements. However, several studies have suggested a role for the piRNA-PIWI axis in somatic cells, including somatic stem cells. Dysregulated expression of piRNAs and PIWI proteins in human tumors implies that, analogously to their roles in undifferentiated cells under physiological conditions, these molecules may be important for cancer stem cells and thus contribute to cancer progression. We provide an overview of piRNA biogenesis and critically review the evidence for the role of piRNA-PIWI axis in cancer stem cells. In addition, we examine the potential of piRNAs and PIWI proteins to become biomarkers in cancer.